2008
DOI: 10.1038/eye.2008.122
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective outcomes in comparing three different aspheric intraocular lens implants with their spherical counterparts

Abstract: Purpose To look for objective and subjective differences between three types of aspheric intraocular lens implants and their spherical counterparts. Methods Thirty patients were randomised to receive one of six lens implants including three aspheric lenses and their spherical counterparts. Pre and postoperative testing was carried out including visual acuity, contrast sensitivity and wavefront analysis. All patients were asked to fill in a visual function questionnaire (modification of cataract TyPE) to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
(16 reference statements)
3
12
0
Order By: Relevance
“…In comparisons of the Tecnis Z9000 or Z9001 aspheric IOL and spherical IOLs, a few studies 16,19 found an increase in corrected distance visual acuity (CDVA), and most report similar outcomes. 15,[20][21][22][23]25,29,30,38,43,44,[47][48][49][50]77 Similar CDVAs were also reported for the AcrySof IQ SN60WF IOL 29,[32][33][34][35][36][37][38][39][40][41]45,46 and other aspheric IOLs. 29,31,37,38 The results in studies of contrast sensitivity are not as consistent as the visual acuity results.…”
Section: Discussionsupporting
confidence: 74%
“…In comparisons of the Tecnis Z9000 or Z9001 aspheric IOL and spherical IOLs, a few studies 16,19 found an increase in corrected distance visual acuity (CDVA), and most report similar outcomes. 15,[20][21][22][23]25,29,30,38,43,44,[47][48][49][50]77 Similar CDVAs were also reported for the AcrySof IQ SN60WF IOL 29,[32][33][34][35][36][37][38][39][40][41]45,46 and other aspheric IOLs. 29,31,37,38 The results in studies of contrast sensitivity are not as consistent as the visual acuity results.…”
Section: Discussionsupporting
confidence: 74%
“…Aspheric IOLs were designed to compensate for the positive spherical aberration of the cornea. Although some studies 1,4,13,[22][23][24][25][26][27] report that the reduction in postoperative spherical aberration by aspheric IOLs improved visual function, other studies 21,37 report no significant difference in visual function between spherical IOLs and aspheric IOLs. The limitations of these studies were a fixed pupil diameter and a lack of assessment of individual visual function and spherical aberration considering individual pupil diameter; this is important because corneal spherical aberration varies widely in the population 7 and pupil diameter, which affects the amount of spherical aberration, also widely among individuals.…”
Section: Discussionmentioning
confidence: 89%
“…The limitations of these studies were a fixed pupil diameter and a lack of assessment of individual visual function and spherical aberration considering individual pupil diameter; this is important because corneal spherical aberration varies widely in the population 7 and pupil diameter, which affects the amount of spherical aberration, also widely among individuals. 28 Moreover, studies 1,4,13,[22][23][24][25][26][27] show that aspheric IOLs improve contrast sensitivity over that with spherical IOLs; however, the amount of spherical aberration to optimize the visual function remains unknown. We believe it is imperative to assess the efficacy of correcting spherical aberration by evaluating the relationship between individual spherical aberration, HOAs, and visual function.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, results in recent studies show discrepancies in terms of whether aspheric IOLs provide better postoperative visual function than spherical IOLs. 1,4,13,[20][21][22][23][24][25][26][27] These studies are limited by the use of a fixed pupil diameter (from 4.0 to 6.0 mm) and by not including an assessment of individual visual function when evaluating the amount of spherical aberration according to individual pupil diameter. In some patients with small pupils (eg, 3.0 mm) under mesopic conditions, the spherical aberration is too small to affect postoperative visual function.…”
mentioning
confidence: 99%